Identifying the Impact of Using Simulation Programs on Acquiring Physics Concepts for Female Students in Grade 11 - Nasser S. Almzidi; Ali H. Al Shuaili (Sultan Qaboos University, 2017)
This study aims at identifying the impact of using Simulation programs on acquiring physics concepts, and development of lab activity skills. The sample consisted of (54) female students in grade 11 in the General Education at schools in Al-Batinah North Governorate. The sample was divided into two groups: The experimental group (n=28) that studied physics using simulation, and the control group (n=26) that studied the same material but using the traditional method of teaching. To achieve the study aims three tools were prepared: The Physics Concepts Test, the Laboratory Work Skills Test, and Laboratory Work Skills Observation Card. After conducting the tests before and after the study treatment, and observing the student while working on the experiments, the study results showed that no statistical differences was indicated between the experimental group and the control group in terms of gain of physics concepts, and all lab activity skills. In addition, the results of the Laboratory Work Skills Observation Card showed that simulation programs made the student make most of the lab activity skills. In view of the findings of the study, some suggestions and recommendations were proposed for future research.